Event-triggered sliding mode control of networked control systems with Markovian jump parameters. (March 2021) - Su, Xiaojie; Wang, Chunlian; Chang, Hongbin; Yang, Yue; Assawinchaichote, Wudhichai
Abstract: This paper deals with sliding mode control for networked Markovian jump systems with partially-known transition probabilities via an event-triggered scheme to reduce network bandwidth usage and save network resources. First, based on the analysis of event-triggered scheme and sliding mode control, a corresponding time-delay system model is constructed by investigating the effect of the network transmission delay. Then, the less-conservative mean-square asymptotic stability of the overall closed-loop system is established. Sufficient conditions are obtained to co-design both the switching function and trigger parameters. Simultaneously, a novel control scheme is used to handle the Markovian jump parameters. Cases of completely known or unknown probabilities transition probabilities are also presented. Furthermore, the reachability of the sliding surface under the event-triggered sliding mode controller is analyzed using the Lyapunov stability theory. Finally, simulation results are provided to verify the effectiveness of the proposed design schemes.